Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
ISI Document Delivery No.: 089JE Times Cited: 18 Cited Reference Count: 16 Cited References: ANDO T, 1982, REV MOD PHYS, V54, P437, DOI 10.1103/RevModPhys.54.437 ANDO T, 1989, HIGH MAGNETIC FIELDS, V2, P164 Ashcroft NW, 1976, SOLID STATE PHYS, P1 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Cerne J, 2000, PHYS REV B, V61, P8133, DOI 10.1103/PhysRevB.61.8133 COLERIDGE PT, 1991, PHYS REV B, V44, P3793, DOI 10.1103/PhysRevB.44.3793 Dorozhkin PS, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2035883 Knap W, 2002, APPL PHYS LETT, V81, P4637, DOI 10.1063/1.1525851 Knap W, 2002, APPL PHYS LETT, V80, P3433, DOI 10.1063/1.1473685 Kukushkin IV, 2005, APPL PHYS LETT, V86, DOI 10.1063/1.1856143 MADELUNG O, 1996, SEMICONDUCTORS BASIC, P109 MCKNIGHT SW, 1987, INFRARED PHYS, V27, P327, DOI 10.1016/0020-0891(87)90074-1 Peralta XG, 2002, APPL PHYS LETT, V81, P1627, DOI 10.1063/1.1497433 Sadofyev YG, 2002, APPL PHYS LETT, V81, P1833, DOI 10.1063/1.1504882 Shaner EA, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2128057 ZAWADZKI W, 1974, ADV PHYS, V23, P435, DOI 10.1080/00018737400101371 Kabir, N. A. Yoon, Y. Knab, J. R. Chen, J. -Y. Markelz, A. G. Reno, J. L. Sadofyev, Y. Johnson, S. Zhang, Y. -H. Bird, J. P. Bird, Jonathan P/G-4068-2010 Bird, Jonathan P/0000-0002-6966-9007; Markelz, Andrea/0000-0003-0443-4319 18 15 Amer inst physics Melville
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz